(NgORQ^IJ SNEG(B: [(NrOMAN(B] /s - (NbONDAREW(B, (N`RIJs ((NmOSKWA(B: s (NwOENNOE IZDATELXSTWO(B, s, 1984)
(NrOMAN `RIQ bONDAREWA (B"(NgORQ^IJ SNEG(B" (NPOSWQ]EN ODNOJ IZ GEROI^ESKIH STRANIC wELIKOJ oTE^ESTWENNOJ WOJNY (B- (NsTALINGRADSKOJ BITWE(B.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs; (NwOENNYJ ROMANs